A High-Throughput Cellular Screening Assay for Small-Molecule Inhibitors and Activators of Cytoplasmic Dynein-1-Based Cargo Transport. (October 2020) - Vincent, John; Preston, Marian; Mouchet, Elizabeth; Laugier, Nicolas; Corrigan, Adam; Boulanger, Jérôme; Brown, Dean G.; Clark, Roger; Wigglesworth, Mark; Carter, Andrew P.; Bullock, Simon L.
Cytoplasmic dynein-1 (hereafter dynein) is a six-subunit motor complex that transports a variety of cellular components and pathogens along microtubules. Dynein's cellular functions are only partially understood, and potent and specific small-molecule inhibitors and activators of this motor would be valuable for addressing this issue. It has also been hypothesized that an inhibitor of dynein-based transport could be used in antiviral or antimitotic therapy, whereas an activator could alleviate age-related neurodegenerative diseases by enhancing microtubule-based transport in axons. Here, we present the first high-throughput screening (HTS) assay capable of identifying both activators and inhibitors of dynein-based transport. This project is also the first collaborative screening report from the Medical Research Council and AstraZeneca agreement to form the UK Centre for Lead Discovery. A cellular imaging assay was used, involving chemically controlled recruitment of activated dynein complexes to peroxisomes. Such a system has the potential to identify molecules that affect multiple aspects of dynein biology in vivo. Following optimization of key parameters, the assay was developed in a 384-well format with semiautomated liquid handling and image acquisition. Testing of more than 500, 000 compounds identified both inhibitors and activators of dynein-based transport in multiple chemical series. Additional analysis indicated that many of the identified compounds do not affect the integrity of the microtubule cytoskeleton and are therefore candidates to directly target the transport machinery.